Synthesis of highly tetrahedral amorphous carbon by mixed-mode HiPIMS sputtering - Ganesan, R.; McCulloch, D.; Marks, Nigel; Tucker, M.; Partridge, J.; Bilek, M.; McKenzie, D. (2015)
Tetrahedral amorphous carbon films with an sp 3 content of 80% have been produced by high power impulse magnetron sputtering (HiPIMS) operating in a mixed sputtering/arc mode. In this mode, short-lived cathode spots form in the magnetic racetrack and produce large numbers of carbon ions. The spots move rapidly, inhibiting the formation of macroparticles. An argon pressure below 2.5 mTorr was critical for obtaining films with high sp 3 content, high stress, large Tauc gap and symmetrical Raman spectra, and all four quantities were strongly correlated.